PENGUATAN KELEMBAGAAN PENGAWAS PEMILU DALAM PENYELENGGARAAN PEMILIHAN KEPALA DAERAH DAN WAKIL KEPALA DAERAH - Erwin Prima Rinaldo (Universitas Lampung, 2016)
AbstractDemocracy substance is “raison de etre” on regulating direct election system and it’s position about implementation principle of the state by law. Based on evaluating in 2005 until 2014, conducted alteration for implementation system, who reflected alteration policy purpose about election supervisor institute. An aim of this research is (a) to explain the direction of reinforcement supervisor election institute policies based on Law Number 1 of 2015 attached its alteration, and (b) the impact of reinforcement concerning institutional capacity. This research used juridical normativism method, through statue approach, conceptual and institutional in an integrative manner. Data resources used a secondary material with qualitative analysis technique.These research conclude the direction policies about reinforcement has been formed by enforcement duties, authority, obligation, character and function head for transformation as control institution. An impact about institution capacity is forming mechanism not including for enforcement capacity orientation, asymmetry on implementation administrative function, procedure, and finances ordering, rather regulation quality from Bawaslu with the result obstruction concerning the effectiveness of institutionally implementation function. Suggestion is (a) upgrading typology of Election Supervisor Board Province and alteration characteristic Election Supervisor Kabupaten/Kota become permanent institution or increasing quality, quantity and qualification human resources, (b) correction regulating about procedure and duty on pieces as integrative, also (c) completing regulation about observatory implementation function based on norm and rule pursuant to election ordinance. Keywords: Institusional Reinforcement, Election Supervisor and Local Election AbstrakSubstansi demokrasi merupakan raison de etre Pilkada secara langsung dan menegaskan kedudukannya atas implementasi prinsip negara hukum. Berdasarkan evaluasi tahun 2005 s.d 2014, dilakukan perubahan sistem penyelenggaraan yang merefleksikan perubahan arah kebijakan terhadap kelembagaan pengawas Pemilu. Tujuan penelitian ini (a) menjelaskan arah kebijakan penguatan kelembagaan pengawas Pemilu berdasarkan Undang-Undang Nomor 1 Tahun 2015 beserta peraturan perundangan perubahannya, dan (b) dampak penguatan terhadap kapasitas lembaga. Penelitian ini menggunakan metode yuridis normatif, melalui pendekatan undang-undang, konseptual dan kelembagaan secara integratif, menggunakan sumber data sukunder dengan teknik analisis kualitatif. Disimpulkan penguatan kelembagaan diwujudkan melalui penguatan tugas, kewenangan, kewajiban, peran dan fungsi kelembagaan yang mengarah transformasi fungsi sebagai institusi kontrol. Dampak terhadap kapasitas lembaga diantaranya mekanisme pembentukan belum berorientasi penguatan kapasitas, kesenjangan penatalaksanaan fungsi administrasi, tata kerja dan penatausahaan keuangan, serta lemahnya kualitas Peraturan-Peraturan Bawaslu yang menghambat efektifitas fungsi kelembagaan. Disampaikan saran (a) peningkatan tipelogi Bawaslu Provinsi dan perubahan kelembagaan ditingkat Kabupaten/Kota menjadi bersifat tetap dan/atau peningkatan kualitas, kuantitas dan kualifikasi SDM (b) pembenahan regulasi tata kerja dan uraian tugas secara integratif, serta (c) penyempurnaan regulasi pengawasan Pemilu berdasarkan norma dan kaidah peraturan perundang-undangan. Kata Kunci: Penguatan Kelembagaan, Pengawas Pemilu dan Pilkada